Sistem Pendukung Keputusan Penentuan Gaya Belajar Siswa Menggunakan Metode Profile MatchingSistem Pendukung Keputusan Penentuan Gaya Belajar Siswa Menggunakan Metode Profile Matching - Suseno, Endra; Syakira, Elsa; Trisudarmo, Ragel (Insearch: Information System Research Journal, 2024)
An educational institution located in Kuningan Regency, specifically in Jalaksana District, has implemented the independent curriculum with differentiated learning to meet students' learning needs based on their learning styles. However, determining learning styles requires a lengthy process and time. Moreover, the criteria used for determination have not yet referred to students' learning styles, resulting in inaccurate identification of students' learning styles. To address this issue, a decision support system using the profile matching method is employed, which compares students' actual data values with the expected profile to identify competency gaps. This method uses criteria such as communication, learning, memory, and attitude. The goal is to facilitate the school in determining students' learning styles. The outcome of this study is the generation of recommendations for students' learning styles calculated using the profile matching method. The calculations yielded the highest score of 4.6 for the visual learning style and the lowest score of 3.6 for the auditory learning style. The accuracy rate obtained is 97.92% or in another word it can be said that it is effective and accurate for the school to use in determining students' learning styles.